Effective Nonverbal Communications and English Language Classrooms - Sahar Najarzadegan; Azizollah Dabaghi (Research in English Language Pedagogy, 2014)
Nonverbal communication (NVC) plays a highly important role in different aspects of human life. Regarding teachers, however, it is more important, and they should be very cautious about what type of NVC they use and how they perform it in their teaching process. While practical tangible teaching techniques driven from nonverbal behaviors can help English language teachers incorporate this essential element into their classrooms, little attention has been given to this area. This article tries to shed light on the often neglected, unexplored area of research concerning nonverbal communication. It begins by mentioning the indispensable role of NVC in the communicative process and then explaining different forms and functions of these NVBs, attempt has been made to incorporate those NVCs into language classes and give some practical techniques to be considered in the classrooms, in order for the learners to be as Pennycook (1985) puts it "not only bilingual but also bi- kinesics".